AcrAB Efflux Pump Plays a Crucial Role in Bile Salts Resistance and Pathogenesis of Klebsiella pneumoniae - Rundong Shu; Ge Liu; Yunyu Xu; Bojun Liu; Zhi Huang; Hui Wang (Antibiotics)
Bile salts possess innate antibacterial properties and can cause significant damage to bacteria. To survive in the mammalian gut, Klebsiella pneumoniae has developed mechanisms to tolerate bile salts; however, the specific mechanisms remain unclear. Transposon library screening revealed that the efflux pump AcrAB is involved in bile salt resistance. acrA and acrB mutants exhibited high sensitivity not only to bile salts but also to SDS and various antibiotics, with a switch-loop, comprising residues G615, F616, A617, and G618, proving to be crucial in this process. A colonization defect of acrA and acrB mutants was demonstrated to be located in the mouse small intestine, where the bile salt concentration is higher compared to the large intestine. Additionally, both acrA and acrB mutants displayed reduced virulence in the Galleria mellonella model. In conclusion, our results suggest that the Resistance-Nodulation-Cell Division efflux pump serves as a critical determinant in the pathogenesis of K. pneumoniae through various aspects.